Whey Proteins Solubility Curves at Several Temperatures Values - Pelerine, Daniela Helena Guimarães; Santos Gomes, Maria Thereza de Moraes (Ciência e Natura, 2008)
This work showed the whey proteins solubility curves, accordingwith temperature and pH conditions. The product constituted of a wheyprotein isolate obtained from cow milk (ALACENTM 895), acquired byNew Zeland Milk Products Ltd. There is a straight analogy between foulingand protein unfolding when milk derived fluids are processed in equipmentsof heat exchangers, where whey proteins are unfolded in an irreversibleway, exposing hidrophobic groups, and they become insoluble and formaggregates. An integrated study was conducted on the effects of temperatureand pH on the solubility of whey proteins. The solubility was determinedexperimentally in the temperature range of 40-90 °C, and pH range of 5.0- 6.8. The results showed that, both the temperature and pH influenced inthe protein solubility; besides, the solubility values were minimum at thepH 5.0 for all temperature values. It was also observed that solubilitydecreased with temperature increased.